Updates in Pancreatic Neuroendocrine Carcinoma - Alsamarai, Susan; Libutti, Steven K; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Pancreatic neuroendocrine tumors display a range of clinical presentations and outcomes. Surgical resection remains the only potentially curative approach for primary tumors, and is also associated with a survival benefit for hepatic metastases as well. Data presented at the American Society of Clinical Oncology (ASCO) Annual Meeting this year suggest that targeted agents may also play a role in advanced disease. Sunitinib, which targets VEGF-1, 2 and 3 and PDGF seems to be a well tolerated treatment for advanced tumors. The mTOR inhibitor everolimus when combined with the VEGF inhibitor bevacizumab, resulted in measurable responses. The combination of bevacizumab and cytotoxic chemotherapy also shows potential. Image: Smilow Cancer Hospital at Yale. New Haven, CT, USA.